INVESTIGATION OF GAMMA-RAY SHIELDING PERFORMANCE OF BOROSILICATE GLASSES DOPED WITH TiO2 USING PHY-X/PSD AND XCOM SOFTWARE (FUDMA JOURNAL OF SCIENCES, 2025)
Growing demand for eco-friendly gamma-ray shielding materials has inspired interest in borosilicate glasses enhanced with heavy metal oxides (HMOs). This study uniquely evaluates the influence of borosilicate glasses doped with TiO across a broad energy range Spectrum. The gamma-ray shielding performance of TiO-doped borosilicate glasses with the composition of 30B2O3(70-x)SiO2xTiO2 glass system was investigated (where x = 0, 1, 2, 3, 4 and 5mol%). Shielding parameters mass attenuation coefficient (MAC), half-value layer (HVL), tenth-value layer (TVL), mean free path (MFP), and effective atomic number (Zeff) were calculated using the Phy-X/PSD software over photon energies from 0.015 15MeV. The mass attenuation coefficient results obtained were cross-verified with XCOM database values, demonstrating close correlation and validating the computational accuracy. The results revealed that increasing TiO concentration led to a slight but consistent enhancement in gamma-ray shielding compared to the undoped sample. GDTi5 exhibited the best performance, with a MAC of 5.400 cm/g, Zeff of 13.05, HVL of 0.0497 cm, and MFP of 0.070 cm at 0.015 MeV. The order of shielding effectiveness was GDTi5 > GDTi4 > GDTi3 > GDTi2 > GDTi1 > undoped. These TiO-doped borosilicate glasses, especially GDTi5, are suitable for applications requiring moderate radiation protection and optical transparency, such as diagnostic imaging rooms, nuclear laboratory windows, and portable protective screens.
Keywords: Gamma-ray shielding; Phy-X/PSD; WinXCom; Mass Attenuation Coefficient (MAC); Radiation protection; Heavy Metal Oxide (HMO)